Unbroken cowboy - Yates, Maisey (Yates, Maisey. Gold Valley novel., 2019)
Dane Parker traded in his trailer-park roots for glory as a bull rider. But when a serious injury sidelines him for months, it<U+2019>s the first time he can<U+2019>t just pull himself up by his bootstraps. The last thing he wants to deal with is sweet family friend Bea treating him like one of her wounded animals<U+2014>or the unexpected attraction that suddenly flares between them. Beatrix Leighton has loved Dane for years, while he<U+2019>s always seen her as another sister. When she enlists his help to start her animal sanctuary, she thinks it will give him purpose. Instead, it brings all the desire she feels for him to the boiling point. Bea<U+2019>s father taught her early on that love means loss. But could her forbidden crush turn into a love that will last a lifetime?